2020
DOI: 10.1002/smll.202004654
|View full text |Cite
|
Sign up to set email alerts
|

A pH‐Responsive Polymer‐CeO2 Hybrid to Catalytically Generate Oxidative Stress for Tumor Therapy

Abstract: effect), a lower pH value, as well as a high level of oxidative stress. [4-9] Especially, the overproduction of reactive oxygen species (ROS) induces a serious oxidative stress, which is strongly implicated to various tumors. [8,9] In addition, a high ROS level is also considered to be an endpoint of the alteration of several important metabolic pathways in tumors. [8-11] Thus, modulation of the intratumor ROS level, either by scavenging ROS or increasing ROS, is a promising approach to anticancer therapy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 63 publications
(153 reference statements)
0
42
1
Order By: Relevance
“…There are also examples that use Ce‐containing nanoagents for CDT. [ 19,345,346 ] For example, Xu et al. designed biocompatible PDA/NH 4 HCO 3 ‐coated and DOX‐loaded hollow CeO 2 NPs (termed PDAC NPs) for the combinational PTT/chemotherapy/CDT against cancer.…”
Section: Applications Of Cdt In Anticancer and Antibacterial Therapiesmentioning
confidence: 99%
“…There are also examples that use Ce‐containing nanoagents for CDT. [ 19,345,346 ] For example, Xu et al. designed biocompatible PDA/NH 4 HCO 3 ‐coated and DOX‐loaded hollow CeO 2 NPs (termed PDAC NPs) for the combinational PTT/chemotherapy/CDT against cancer.…”
Section: Applications Of Cdt In Anticancer and Antibacterial Therapiesmentioning
confidence: 99%
“…The pH factor plays an important role in the reaction catalyzed by nanoscale cerium oxide. For example, Asati and coworkers [59] found that the simulated oxidase activity of nanoscale cerium oxide is highly dependent on environmental pH, and has the strongest activity in acidic acetate buffer, which can be attributed to the protonation effect of nanoscale cerium oxide at low pH [59,69]. This is based on the fact that nanoscale cerium oxide has strong peroxidase and oxidase activities under acidic conditions and strong SOD and CAT activities under neutral or alkaline conditions [70].…”
Section: Surrounding Environmentsmentioning
confidence: 99%
“…[20] This ability to oxidize substrates such as 3′,3′,5′,5′-tetramethylbenzidine (TMB), 2,2-azinobis (3-ethylbenzothizoline-6-sulfonic acid) (ABTS), o-phenylenediamine, and dopamine have been used for creating pH-or redox-responsive sensors for cancer detection, [21] dopamine sensing, [22] and even generate oxidative stress for tumor therapy. [23] These oxidative properties (oxidase-like or peroxidase-like) have enabled multiple biomedical applications for nanoceria, [24] dividing the scientific community between its pro-oxidant and antioxidant properties. This is especially important for future biomedical applications of nanoceria wherein only anti-oxidative properties are required.…”
Section: Introductionmentioning
confidence: 99%